Design of temperature measuring instrument using NTC thermistor of Fe2TiO5 based on microcontroller ATmega 328 - Munifah, S S; Wiendartun; Aminudin, A (Journal of physics. Conference series, 2019)
Thermistor is one of temperature sensor which works based on resistance changes and can be used as a temperature measuring instrument. In a previous study, an NTC thermistor of Fe2TiO5 was made in the form of raw pellet without doping, sintered at a temperature of 1200°C for 2 hours in oxygen. A thermistor constant value that obtained from the characterization process is 3821.65 K. This result showed that the thermistor has good quality because it has relatively large constant thermistor. Fe2TiO5 is one of semiconductors that used as basic material for main fabrication component of NTCs as temperature sensor. In this study, temperature measuring instrument using NTC thermistor of Fe2TiO5 sensor based on microcontroller ATMEGA 328. The NTC is assembled in parallel with a fixed resistor and then assembled on ICLM741 and microcontroller ATMEGA 328. The magnitude of the resistor varies at 1 MΩ, 2 MΩ, and 3 MΩ with each resistor having a tolerance value of 1%. From these variations we can get sensitivity value with the value of 0.00688 MΩ/°C; 0.0133 MΩ/°C, and 0.02195 MΩ/°C, respectively. As result, this temperature measuring instrument shows good sensitivity when assembled in parallel using 3 MΩ fixed resistor with a tolerance value of 1% and capable of measuring the temperature in the range 26°C - 103.2°C.